The Relationship among Zakat Maal, Altruism and Work Life Quality - Ardian Adhiatma; Olivia Fachrunnisa (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
The purpose of this study is to analyze the effect of zakat maal expenditure behavior on work altruism and quality. The study was conducted at a higher education institution that practices a strong culture in religious activities. A total of 223 respondents were involved in this study. Data were obtained using a questionnaire and analyzed using the PLSPM of SmartPLS 3.2.8. The results of this study showed that compliant employees’ payment of zakat maal could increase work altruism and quality of work-life, thereby increasing their performance. The behavior of zakat maal payment in this study is evidenced by the existence of a workplace, that supports the implementation of the obligations of a Muslim, so as to increase their awareness in paying zakat when reaching the nishab. Encouragement from the organization about this matter ultimately increases work altruism which can help improve work productivity and make employees feel they have a better and more balanced work life.